Gambaran Kualitas Hidup Penderita Diabetes Melitus di Desa Adow Kabupaten Bolaang Mongondow Selatan - Kolintama, Tahsya V. S.; Pongoh, Lucyana L.; Tengker, Anita C. C.; Sudirham, Sudirham; Manoppo, Jonesius E.; Makadada, Fredrik A. (Yayasan Syalom Cipta Sumikolah, 2025)
Diabetes Mellitus is a chronic disease that affects various aspects of patients' lives, including physical, psychological, social, and environmental aspects. Health center data show an increase in Diabetes Mellitus cases from 21 patients in 2023 to 60 patients in 2024. This increase indicates the importance of understanding the quality of life of patients in order to support prevention and disease management efforts.This study aimed to describe the quality of life of patients with Diabetes Mellitus based on physical, psychological, social relationship, and environmental aspects, as well as satisfaction and concerns related to the disease. This study used a quantitative descriptive method with a total sampling technique involving 60 patients with Diabetes Mellitus. Data were collected using the WHOQOL-BREF questionnaire and the Diabetes Quality of Life (DQOL) questionnaire. Data analysis was carried out using univariate analysis in the form of frequency distribution and percentages. The results showed that the quality of life of patients with Diabetes Mellitus in various aspects was mostly in the poor category. In the physical health aspect, the majority of respondents were in the poor category with 43 people (71.7%). In the psychological aspect, most respondents were in the moderate category with 41 people (68.3%). In the social relationship aspect, the majority of respondents were in the poor category with 37 people (61.7%), while in the environmental aspect most respondents were in the moderate category with 36 people (60%). However, based on the DQOL questionnaire, the diabetes-specific quality of life was in the high category (100%), indicating that respondents had good self-efficacy and high satisfaction in managing their disease.